DESAIN DAN IMPLEMENTASI RESTful WEB SERVICES UNTUK INTEGRASI DATA DAN APLIKASI - Herfandi Herfandi; M Julkarnain; Muhammad Hanif (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
Industry (business) in the culinary field in Indonesia is a business that is experiencing very rapid growth. Improving the quality of service in a business will have implications for the maximum profit obtained. The right technology to connect various platforms is web services. Geprek Chicken Dinner management uses two different applications for its business processes. This of course hampers business processes and requires time and energy which causes business processes to be not optimal. Therefore, the purpose of research on the design and implementation of RESTful web services at Geprek Chicken Dinner. This research produces RESTful web services applications with access token and API key features as a security system with extreme programming development methods. the black box method involves auditors and IT experts getting successful conclusions from various types of tests. This application is expected to be able to serve as a base for all processed data and as a liaison between applications that will be used by management, so that the applications used are integrated with each other.